Early and late implant failure of submerged versus non‐submerged implant healing: A systematic review, meta‐analysis and trial sequential analysis. (10th May 2018) - Troiano, Giuseppe; Lo Russo, Lucio; Canullo, Luigi; Ciavarella, Domenico; Lo Muzio, Lorenzo; Laino, Luigi
Abstract: Introduction: The aim of this systematic review was to analyse current evidence regarding differences in early and late implant failure as well as in marginal bone level (MBL) changes between submerged and non‐submerged healed dental implants. Methods: PUBMED, SCOPUS, EMBASE and Web of Science databases were searched for prospective randomized and non‐randomized controlled studies addressing direct comparison between submerged and non‐submerged implant healing, without performing immediate loading. Early and late implant failure (before or after 6 months from implant placement, respectively) together with MBL were the investigated outcomes. Risk of bias assessment was performed using the Cochrane Collaboration Tool for Randomized clinical trials. Meta‐analysis was performed and the power of the meta‐analytic findings determined by trial sequential analysis (TSA). Results: Eleven studies met the inclusion criteria and were included in the review. Results of this systematic review revealed a small higher rate (2%) of early implant failure when a non‐submerged healing approach is performed. Late implant failure appears not to be different in submerged or non‐submerged healing, but the power of evidence, as determined by TSA, is not high. If we consider MBL changes at 1 year from implant load, it seems that non‐submerged healing may better preserve marginal bone, although with a small effect size (0.13 mm). Conclusions: Implants placed with a non‐submerged technique have a higher risk (2%) of early failure. The power of the evidence about the effects on MBL is low, but present results seem to favour non‐submerged healing, although with a very small effect size.